The Effect of Entrepreneurship and Craft Subject Learning, Income Expectations, and Family Environment on Entrepreneurial Interest among Eleventh-Grade Students at SMAN 1 Papar - Faizal Wiyadi; Bayu Surindra; Elis Irmayanti (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
High unemployment and limited employment opportunities underscore the importance of promoting entrepreneurship as an alternative career pathway for young people. This study examined the effects of Entrepreneurship and Craft Subject Learning (PKWU), income expectations, and family environment on entrepreneurial interest among Grade XI students at SMAN 1 Papar. A quantitative approach with a causal-associative design was employed, involving 187 students selected through proportionate stratified random sampling. Data were collected using a Likert-scale questionnaire and analyzed through multiple linear regression using SPSS version 23. The findings demonstrated that PKWU learning, income expectations, and family environment each had a positive and statistically significant effect on entrepreneurial interest. PKWU learning significantly influenced entrepreneurial interest (p = 0.043), as did income expectations (p = 0.026), while family environment emerged as the most dominant predictor (p < 0.001). Simultaneously, the three variables significantly predicted entrepreneurial interest (F = 95.498, p < 0.001), explaining 61.0% of its variance (R² = 0.610). These findings indicate that students’ entrepreneurial interest is shaped by the combined influence of educational, economic, and family-related factors. This study contributes empirical evidence to the development of entrepreneurship education and provides practical implications for schools, families, and policymakers in designing coordinated strategies to strengthen entrepreneurial interest and promote economic independence among young people.